Design Principles for Computing Education in Early Childhood - Rodrigues, Stefane Menezes; Neris, Vânia Paula de Almeida (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
This study addresses the need for clear guidelines to teach computing in early childhood, given young children’s growing exposure to technology. It investigates how to design activities that integrate computational concepts while supporting holistic development. Aimed at teachers planning design processes, these principles ensure children actively collaborate in creating computing tools and that the experience remains meaningful. Derived from thematic analysis of scientific literature and validated by a focus group of computing and early education experts, five principles emerged. Findings demonstrate that linking family experiences to cooperative tasks provides educators foundation to cultivate digital literacy and computing education from the earliest school years.